Colombia : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2015)
Colombia has made impressive strides in reducing poverty and promoting shared prosperity during the last decade. Extreme poverty fell from 17.7 percent in 2002 to 8.1 percent in 2014, while total poverty (including moderate poverty) fell from 49.7 percent in 2002 to 29.5 percent in 2014. The decline implies that 6.2 million people left poverty in the period. The multidimensional poverty rate, which takes into account education, health, labor, childcare, and housing, has also experienced a remarkable decline from 49 percent in 2003 to 21.9 percent in 2014. The number of multidimensional poor declined by 9.8 million. Shared prosperity indicators followed a similar trend, especially after the second half of the decade. Between 2008 and 2013, the income per capita of the bottom 40 percent of Colombians grew at an average rate of 6.6 percent, significantly higher than the national average rate of 4.1 percent for the same period. Economic growth that led to job creation has been the main driver of poverty reduction and shared prosperity gains. The economy sustained an average GDP growth of 4.4 percent during the 2000s, almost 2 percentage points higher than the previous decade. For the period 2002-2013, economic growth explains 73 percent of the reduction in extreme poverty and 84 percent of the reduction in total poverty. Moreover, price stability, and in particular stable food prices contribute to poverty outcomes. As in the case of poverty reduction, labor income growth is the main determinant of shared prosperity in recent years in Colombia. Labor income represents at least fifty percent of income growth for the poorest 10 percent of the population, and up to 70 percent for those in the fourth decile, in the period 2008-2013. This evidence highlights the importance of high growth and low inflation for achieving the World Bank’s twin goals in Colombia.